Characteristics of Bacterial Microbiota in Different Intestinal Segments of Aohan Fine-Wool Sheep - Ma, Yuhao; Deng, Xiaotian; Yang, Xue; Wang, Jiankui; Li, Tun; Hua, Guoying; Han, Deping; Da, Lai; Li, Rui; Rong, Weiheng; Deng, Xuemei (Frontiers in Microbiology, 2022)
The microbial community performs vital functions in the intestinal system of animals. Modulation of the gut microbiota structure can indirectly or directly affect gut health and host metabolism. Aohan fine-wool sheep grow in semi-desert grasslands in China and show excellent stress tolerance. In this study, we amplified 16S rRNA gene to investigate the dynamic distribution and adaptability of the gut microbiome in the duodenum, jejunum, ileum, cecum, colon, and rectum of seven Aohan fine-wool sheep at 12 months. The results showed that the microbial composition and diversity of the ileum and the large intestine (collectively termed the hindgut) were close together, and the genetic distance and functional projections between them were similar. Meanwhile, the diversity index results revealed that the bacterial richness and diversity of the hindgut were significantly higher than those of the foregut. We found that from the foregut to the hindgut, the dominant bacteria changed from Proteobacteria to Bacteroidetes. In LEfSe analysis, Succiniclasticum was found to be significantly abundant bacteria in the foregut and was involved in succinic acid metabolism. Ruminococcaceae and Caldicoprobacteraceae were significantly abundant in hindgut, which can degrade cellulose polysaccharides in the large intestine and produce beneficial metabolites. Moreover, Coriobacteriaceae and Eggthellaceae are involved in flavonoid metabolism and polyphenol production. Interestingly, these unique bacteria have not been reported in Mongolian sheep or other sheep breeds. Collectively, the gut microbiota of Aohan fine-wool sheep is one of the keys to adapting to the semi-desert grassland environment. Our results provide new insights into the role of gut microbiota in improving stress tolerance and gut health in sheep.